Вы находитесь на странице: 1из 26

, . , , .

1.
1. y = f (x) y = F (x),
F (x) = f (x), dF (x) = f dx.
, , .
1. y = F (x) y = F (x) y = f (x).
F (x) F (x) = c,

c . , y = F (x) y = f (x),
F (x) + c .
F (x) + c, F (x) R y = f (x),
f (x) dx. ,
Z
f (x) dx = F (x) + c,

F (x) , c . f (x) dx
, f (x) .
1 ( ).
:
R

1)
f (x) dx = f (x),
R

2) d
f (x) dx = f (x) dx;
R
3) R f (x) dx = f (x) + c,
4) df (x) = f (x) + c.

. ,
. y = f (x) F (x) 1 ,
1) [x0 , x];
2) [x0 , f (x0 )];
3) [x, f (x)];
4) y = f (x) [x, x0 ].
. [x0 , x] x

m = min f (x),
M = max f (x),
[x,x+x]

[x,x+x]


mx 6 F (x) 6 M x,
1 , , .
1

m6

F (x)
6 M.
x

x .
lim m = lim M = f (x),

x0

x0

lim

x0

F (x)
= F (x).
x

,
2 ( ). ,
y = f (x), f (x).
? , , , , .
1. , , , ,
Z
Z
Z
dx
x2
2
dx,
sin x dx,
.
e
ln x

, .

. ,
Z
0 dx = c,
(1)
Z
1 dx = x + c,
(2)
Z
x+1
x dx =
+ c,
(3)
+1
Z
Z
1
dx
dx =
= ln|x| + c,
(4)
x
x
Z
Z
1
dx
dx =
= arctg x + c,
(5)
2
1+x
1 + x2
Z
Z
1
dx

dx =
= arcsin x + c,
(6)
2
2
1

x
1

x
Z
ax
ax dx =
+ c,
(7)
ln a
,
Z
ex dx = ex + c,
(8)
Z
sin x dx = cos x + c,
(9)
Z
cos x dx = sin x + c,
(10)
Z
Z
1
dx
= ctg x + c,
(11)
2 dx =
sin x
sin2 x
Z
Z
dx
1
dx =
= tg x + c.
(12)
2
cos x
cos2 x

, .
2. f (x) g(x) . :
R
R
1) R af (x) dx = a f (x)Rdx, a 6=R 0 .
2) (f (x)R g(x)) dx = f (x) dx R g(x) dx.
3) f (x) dx = F (x) + c, f (ax + b) dx = a1 F (ax + b) + c, a 6= 0 .

2. , , , :
Z X
n
n
X
ai i+1
x
ai xi dx =
+ c,
i+1
i=1
Z
Z i=0
dx
1
dx
x

p
=
= arcsin + c,
x 2
2
2
a
a
1 (a)
a x
Z
Z
dx
1
dx
1
x
= 2
= arctg + c,
x2 + a2
a
1 + ( xa )2
a
a


Z

Z
Z
x a
dx
1
dx
dx
1
+ c,
=

=
ln
x2 a2
2a
xa
x+a
2a x + a
Z
Z
1
1
1
2
cos mx dx =
(1 + cos 2mx) dx = x +
sin 2mx + c,
2
2
4m
Z
Z
1
1
1
sin2 mx dx =
(1 cos 2mx) dx = x
sin 2mx + c.
2
2
4m
3 ( ).
Z
f (t) dt = F (t) + c.

f (g(x))g (x) dx = F (g(x)) + c,

(13)

f (g(x)) dg(x) = F (g(x)) + c.

(14)

3. , , 3.
R
1) sinm x cos x dx. cos x dx = d sin x, , sin x = t,
Z
Z
Z
tm+1
sinm+1 x
sinm x cos x dx = sinm x d sin x = tm dt =
+c=
+ c.
m+1
m+1
R
2)
a2 x2 dx. x = a sin t.
p
a2 x2 = a cos t,
dx = a cos t.

Z p

a2

x2 dx

=a

cos2 t dt = a2

1

t+


1
sin 2t + c.
4

1
1
1 p
a2 sin 2t = a sin t a cos t = x a2 x2 ,
4
2
2
Z p

x
1 p
a2
a2 x2 dx = x a2 x2 +
arcsin + c.
2
2
a

3) :
Z

Z
d sin x
cos x dx
ctg x dx =
=
= ln|sin x| + c.
sin x
sin x

R
4) xdx
. t = x2 + a2 + x.
2 +a2
x=

t2 a
,
2t

dx

=
2
x + a2

x2 + a2 =

t2 + a
,
2t

dx =

t2 + a
dt.
2t

p
dt
= ln|t| + c = ln|x + x2 + a2 | + c.
t

4 ( ). f (x) g(x)

Z
Z

f (x)g (x) dx = f (x)g(x) g(x)f (x) dx,


(15)

f (x) dg(x) = f (x)g(x)

g(x) df (x).

(16)

(15) ( (16), ) .
4. , .
R
1) ln x dx:
Z
Z
Z
ln x dx = x ln x x d ln x = x ln x dx = x(ln x 1) + c.
R
2) arctg x dx:
Z
Z
Z
x dx
arctg x dx = x arctg x x d arctg x = x arctg x
=
x2 + 1
Z
dx2
1
1
= x arctg x ln(x2 + 1) + c.
= x arctg x
2
2
x +1
2
R
R

arcsin x dx arccos x dx.
R
3) x cos x dx.
Z
Z
Z
x cos x dx = x d sin x = x sin x sin x dx = x sin x + cos x + c.
(17)

Z
Z
Z
x sin x dx = x d cos x = x cos x + cos x dx = x cos x + sin x + c.
(18)
R
x2 cos x dx:
Z
Z
Z
Z
2
2
2
2
2
x cos x dx = x d sin x = x sin x sin x dx = x sin x 2 x sin x dx.
R
(18). x2 sin x dx (17).

Z
Z
n
Sn = x sin x dx,
Cn = xn cos x dx.
(19)

Z
Z
Z
n
n
n
Sn = x sin x dx = x d cos x = x cos x + n xn1 cos x dx = nCn1 xn cos x

Cn =

x cos x dx =

x d sin x = x sin x n

Sn = nCn1 xn cos x,

xn1 sin x dx = xn sin x nSn1 ,

Cn = xn sin x nSn1 .

(20)

, (19) , n
.

. .
4)
Z
En = xn ex dx.
(21)

En =
5)

xn dex = xn nEn1 .

Ln,m =

Ln,m

1
=
n+1

ln x dx

n+1

1
=
n+1

n+1

Ln,m =

(22)

xn lnm x dx.

ln x

1
=
n+1

n+1

x


(23)


d ln x =

n+1

ln x m

n+1

ln

xn+1 lnm x mLn,m1


.
n+1

m1


1
x dx ,
x
(24)

1. , (20), (22) (24)


Z
Z
Z
Z
x
P (x) sin x dx,
P (x) cos x dx,
P (x)e dx,
P (x) lnm x dx,
P (x) .
.
5.
Rk =

(x2

dx
,
+ a2 )k

k > 1.

,
Z
Z


x
1
x
x2 dx

x
d
=
+
2k
.
(x2 + a2 )k
(x2 + a2 )k
(x2 + a2 )k
(x2 + a2 )k+1

,
Z
Z
Z
Z
x2 dx
(x2 + a2 ) a2
dx
dx
2
=
dx
=

a
= Rk a2 Rk+1 ,
(x2 + a2 )k+1
(x2 + a2 )k+1
(x2 + a2 )k
(x2 + a2 )k+1
, ,
1
x
2k 1
Rk+1 = 2 2
+
Rk .
(25)
2
k
ka (x + a )
2ka2

R1 =
,

1
a

arctg xa , , (25), Rk k.
1
2a2
1
R3 = 2
4a
R2 =

x
1
x
+ 2 arctg ,
2
+a
2a
a
x
3
x
3
x
2
+ 4 2
+ 5 arctg
2
2
2
(x + a )
8a x + a
8a
a

x2

(26)
(27)

..

2.
. ,
, ,
Pn (x)
a0 + a1 x + + an xn
,
n, m > 0,
(28)
=
Qm (x)
b0 + b1 x + + bm xm
.. .
-, , :

R(x) =

Qm (x) = bm (x r1 )n1 . . . (x rk )nk (x2 + p1 x + q1 )m1 . . . (x2 + ps x + qs )ms ,

(29)

n1 , . . . , nk , m1 , . . . , ms , r1 , . . . , rk Qm (x), p1 , q1 , . . . , ps , qs ,
p2i 4qi < 0,

i = 1, . . . , s.

-, , , Pn (x) Qm (x)
, (29)
R(x) = Sk (x) +

Tl (x)
,
Qm (x)

(30)

l (x)
Sk (x) Tl (x) , QTm
(x) , .. l < m.
, , :

5.
nj
k X
X
i=1 j=1

mj

X X Mij x + Nij
Aij
+
,
(x rj )j
(x2 + pj x + qj )j

(31)

i=1 j=1

(29).
(31) .
, ,
(30), (31) ( ), :
A
,
xr
Mx + N
= 2
,
x + px + q

A
,
(x r)k
Mx + N
= 2
,
(x + px + q)k

R11 =

R1k =

R21

R2k

k > 1 d = q p4 > 0.

Z

A dx
= A ln|x r| + c
xr

(32)

A
1
A dx
=

+ c.
(33)
k
(x r)
k 1 (x r)k1
R21 R2k , ,

p 2 
p2 
x2 + px + q = x +
+ q
2
4

r
p2
p
a= q ,
x + = t.
(34)
4
2

Z
Z
Z
Z

M t + (N M2p )
Mx + N
M
2t dt
Mp
dt
dx =
dt =
+ N
=
2
2
2
2
2
2
x + px + q
t +a
2
t +a
2
t + a2
1
Mp
t
M
=
ln(t2 + a2 ) +
N
arctg + c.
2
a
2
a
,
Z
2N M p
2x + p
Mx + N
M
arctg
+ c.
(35)
dx =
ln(x2 + px + q) + p
2
2
x + px + q
2
4q p2
4q p
Z


Z
Z
Z
Z

M t + (N M2p )
Mx + N
M
2t dt
Mp
dt
dx =
dt =
+ N
.
2
k
2
2
k
2
2
k
2
(x + px + q)
(t + a )
2
(t + a )
2
(t + a2 )k

M
1

+ c,
2
2(k 1) (x + px + q)k1

(25) 5.
, , :
1) (29);
2) (31).
, m > 4, , . ,
. .
6.

2x2 + 2x + 13
(x 2)(x2 + 1)2
.
2x2 + 2x + 13
A
Bx + C
Dx + E
=
+ 2
+ 2
,
2
2
(x 2)(x + 1)
x2
x +1
(x + 1)2
A, B, C, D E . ,
2x2 + 2x + 13 = A(x2 + 1)2 + (Bx + C)(x2 + 1)(x 2) + (Dx + E)(x 2).

x ,
x4 A + B = 0,
x3 2B + C = 0,
x2 2A + B 2C + D = 2,
x1 2B + C 2D + E = 2,
x0 A 2C 2E = 13.
(, ), ,
A = 1,

B = 1,

C = 2,

D = 3,

E = 4,

1
2x2 + 2x + 13
x+2
3x + 4
=
2
2
.
2
2
(x 2)(x + 1)
x 2 x + 1 (x + 1)2

,
Z

2x2 + 2x + 13
1 3 4x 1 (x 2)2
dx
=

+ ln 2
4 arctg x + C.
(x 2)(x2 + 1)2
2 x2 + 1 2
x +1

, . , , .. , ,
. , , , .

 q
. R x, m x+
x+ , R
, 6= 0,
s
x +
t= m
.
(36)
x +

x=
,
Z


R x,

tm
,
tm

dx
m( )tm1
=
.
dt
( tm )2

Z  m
t  m( )tm1
x + 
dx = R
,t
dt,
x +
tm
( tm )2

(37)

(38)

.. t. , .
7.
Z
Z r
dx
dx
3 x + 1
p
=

3
x1 x+1
(x 1)(x + 1)2

r
x+1
t= 3
.
(39)
x1

t3 + 1
6t2
x= 3
,
dx = 3
.
t 1
(t 1)2

Z r
Z
Z 

dx
dt
t+2
1 
2t + 1 1 t2 + t + 1
3 x + 1
+ ln

= 3
=

dt
=
3
arctg
+ c.
x1 x+1
t3 1
t2 + t + 1 t 1
2
(t 1)2
3
t x (. (39)).

.
Z
xm (a + bxn )p dx,

(40)

a b , m, n p ( ,
). .. 2:
2 XIX .

6. (40) ,

m+1
m+1
,
+p
p,
n
n
.
. , ,
. ,
.
p , , r
m

r
n, R( x), R
.

t = r x.
z = xn
xm (a + bxn )p dx =

m+1
n

m+1
1
(a + bz)p z n 1 dz.
n

1 = q,
Z
Z
1
m
n p
(a + bz)p z q dz.
x (a + bx ) dx =
n

(41)

q , R(z, s a + bz),
s p, R .

s
s
t = a + bz = a + bxn .
, , , (41),

Z 
a + bz  p+q
dx.
z
z
p + q , ,

r
p
s a + bz
s
t=
= axn + b.
z
, , .

8.

Z p
Z
3
1
1 1
1+ 4x

dx == x 2 (1 + x 4 ) 3 dx.
x

1
1
1
m+1
m= , n= , p= ,
= 2,
2
4
3
n
.. 6. s = 3 , ,
q

3
t = 1 + 4 x, x = (t3 1)4 , dx = 12t2 (t3 1)3 dt.
,

Z
1+ 4x
3

dx = 12 (t6 t3 ) dt = (4t3 7)t4 dt + c,


x
7
t x.
Z p
3

10

9.
Z
Z
1
dx

= x0 (1 + x4 ) 4 dx.
4
4
1+x

1
m+1
m = 0, n = 4, p = ,
+ p = 0,
4
n
.. 6.

4
p
1
5
1 + x4
4
4
, x = (t4 1) 4 , dx = t3 (t4 1) 4 dt,
t= x +1=
x
,
Z 2
Z
Z
Z
t dt
dx
1  1
1 
1
dt

dt

=
4
4
2
t 1
4
t+1 t1
2
t +1
1 + x4




p
1 4 x4 + 1 + 1 1
1 t + 1 1
4

arctg
t
+
c
=
ln
arctg(
x4 + 1 + 1) + c.
= ln



4
t 1 2
4 4 x4 + 1 1 2

R(x, ax2 + bx + c).


. .
7.
Z

R(x,

ax2 + bx + c) dx,

(42)

R , .
. -, , , a =
0 , ,
(38),
.
a > 0.
p

t = ax2 + bx + c + a x.

t2 c
a t + bt + c a

x=
,
dx = 2
dt,
2 at + b
(2 a t + b)2
t
.
ax2 + bx + c , x1 x2 .

ax2 + bx + c = a(x x1 )(x x2 ),


t=

ax2 + bx + c
.
x x1

p
x1 t2 ax2
a(x1 x2 )t
2a(x2 x1 )
,
ax2 + bx + c =
, dx =
dt,
2
2
t a
t a
(t2 a)2
.
, . ,
1
b 
b2
ax2 + bx + c =
x
+c .
a
2a
4a
x=

b
a < 0 , .. c 4a
> 0, ,
.


11

10.
Z

dx
.
x + x2 x + 1
7:
x=

t2 1
,
2t 1

dx = 2

t2 t + 1
dt.
(2t 1)2

Z 

t2 t + 1
2
3
3

+
dt =
dt
=
t(2t 1)2
t
2t 1 (2t 1)2
3
1
3
=
+ 2 ln|t| ln|2t 1| + c =
2 2t 1
2
p
p
3
1
3

=
ln|2x + 2 x2 x + 1 1| + 2 ln|x + x2 x + 1| + c.
2 2x + 2 x2 x + 1 1 2

dx

=2
x + x2 x + 1

11.
Z
dx

,
2
a x2
, -, .

a2 x2
t=
.
ax

t2 1
4at dt
x=a 2
,
dx = 2
t 1
(t + 1)2

r
Z
Z
a+x
dx
dt

=2
= 2 arctg t + c = 2 arctg
+ c.
2
t +1
ax
a2 x2
, .
.
R(sin x, cos x).
Z
R(sin x, cos x) dx,

(43)

R , ,
. , t = tg x2 ,
sin x =

2 tg x2
1 + tg2

x
2

2t
,
1 + t2

cos x =

1 tg2
1 + tg2

x
2
x
2

1 t2
.
1 + t2

,
x = arctg t,

dx =

2 dt
1 + t2

(43)
Z 
2t 1 t2  dt
2 R
,
.
1 + t2 1 + t2 1 + t2
Z

12.
Z
1 + a 
1 + a x
(1 a2 ) dx
dt
2
=
(1
a
)
=
arctg
t
+
c
=
arctg
tg
+ c.
1 2a cos x + a2
(1 a)2 + (1 + a)2 t2
1a
1a 2

12

2. , , .
(43) .
13.
Z

sin2 x cos3 x dx

t = sin x:
Z
Z
Z
t3 t5
sin3 x sin5 x
+c=

+ c.
sin2 x cos3 x dx = sin2 x cos2 x d sin x = t2 (1 t2 ) dt =
3
5
3
5
14.

dx
sin x cos2 x

15.
Z

dx
,
sin x cos 2x

t = tg x.
Z
Z
Z
1
dx
t3
2
2
=
(1
+
tg
+ c = tg x + tg3 x + c.
x)
d
tg
x
=
(1
+
t
)
dt
=
t
+
2
3
3
sin x cos2 x

t = cos x.
Z
Z
Z
dx
d cos x
dt
=
=
=
2
2
2
sin x cos 2x
(1

t
)(1
2t2 )
sin x(2 cos x 1)




1 + 2 t 1 1 t
1 + 2 cos x 1 x
1
1





+ c = ln
+ ln

= ln
+ ln tg + c.
2
2 1 2 t 2 1 + t
2 1 2 cos x 2
. ,
Z
Z
Z
x
P (x)e dx,
P (x) sin x dx,
P (x) cos x dx,

P (x) , .

Z
Z
n ax
In = x e sin bx dx,
Jn = xn eax cos bx dx.
n = 0. ,
Z
Z
Z

1
1  ax
eax sin bx dx =
sin bx deax =
e sin bx b eax cos bx dx
a
a

Z
Z
Z

1
1  ax
ax
ax
ax
e cos bx dx =
cos bx de =
e cos bx + b e sin bx dx ,
a
a
..
(
aI0 + bJ0 = a1 eax sin bx,
bI0 + aJ0 = a1 eax cos bx.
,

a sin bx b cos bx ax
b sin bx + a cos bx ax
e ,
J0 =
e .
(44)
2
2
a +b
a2 + b2
,
Z
Z
Z
na
nb
n ax
n a sin bx b cos bx ax
n1 ax
e 2
e sin bx dx + 2
x e sin bx dx = x
x
xn eax cos bx dx
a2 + b2
a + b2
a + b2
I0 =

n ax

x e

cos bx dx =

a sin bx + b cos bx ax
nb
xn
e 2
2
2
a +b
a + b2

..

n1 ax

13

na
sin bx dx 2
a + b2

xn1 eax cos bx dx,

na
nb
a sin bx b cos bx ax
e 2
In1 + 2
Jn1 ,
2
2
2
a +b
a +b
a + b2
nb
na
a sin bx + b cos bx ax
Jn = xn
e 2
In1 2
Jn1 ,
a2 + b2
a + b2
a + b2
,
.
In = xn

3.
, .
.
[a, b] y = f (x), 3. a = x0 6
x1 6 x2 6 6 xn1 6 xn = b .
. i [xi , xi+1 ], i = 0, 1 . . . , n1.
xi = xi+1 xi .
n1
X

(45)

f (i )xi

i=0

, ( ) . = min xi .
i

2. 0 (45), ,
y = f (x) [a, b]
Z b
f (x) dx.
a

y = f (x) , a
b .
3. , 2 ,
:
P
I = lim n1
i=0 f (i )xi .
0

, , > 0 > 0, ,
= max xi < ,
i

n1
X

i=0

f (i )xi I| < .

. [a, b]
mi = min f (x),
[xi ,xi+1 ]

s=

n1
X

mi xi ,

i=0

Mi = max f (x).
[xi ,xi+1 ]

S=

n1
X

Mi xi

i=0

3 , .

14

3. :
1) , , .
2)
s 6 6 S.
3) ,
, .
8 ( ).
,
lim (S s) = 0.
0

(,
).
4. [a, b].
1) .
2) , ,
3) .
. , .
5.
Z a
Z b
f (x) dx =
f (x) dx,
a

f (x) dx = 0.

, [a, b] [b, c], [a, c],


Z b
Z c
Z c
f (x) dx +
f (x) dx =
f (x) dx.
a

.
6. y = f (x) [a, b], y =
kf (x), k , ,
Z b
Z b
kf (x) dx = k
f (x) dx.
a

y = g(x), f (x) g(x)

Z b
Z b
Z b
(f (x) g(x) dx =
f (x) dx
g(x) dx.
a

, .
7. [a, b], a 6 b, y = f (x).
:
1) f (x) > 0 ,
Z

f (x) dx > 0.

15

2) y = |f (x)|
Z b
Z b



f (x) dx 6
|f (x)| dx.

a

3) m 6 f (x) 6 M ,
Z b
m(b a) 6
f (x) dx 6 M (b a).
a

, f (x) 6 g(x) g(x) ,


Z b
Z b
f (x) dx 6
g(x) dx.
a

9 ( ). y = f (x) [a, b] m 6
f (x) 6 M .
Z b
f (x) dx = (b a)
a

, m 6 6 M .

Rb
, a f (x) dx () . , , (,
) , , , . ,
:
Z x
f (t) dt
(46)
F (x) =
a

(, , f t, x
- ). F (x).
8. y = f (t) [a, b]. :
1) y = F (x), (46), x [a, b].
2) y = f (t) , y = F (x)
dF (x)
= f (x).
(47)
dx
, . 2.
1. [a, b]
.
Z x
F (x) =
f (t) dt + c,
(48)
a

c .

2. y = F (x) y = f (x).
Z b
f (x) dx = F (b) F (a).

(49)

4.
Z b
f (x) dx = F (x)|ba .

(50)

(49) ,
.

16

, .
Rb
9 ( ). a f (x) dx, y = f (x) [a, b] . , x = (t)
1) (t) [, ];
2) (t) [a, b] t [, ];
3) () = a () = b;
4) [, ] (t).

Z b
Z
f (x) dx =
f ((t)) (t) dt.
(51)
a

10 ( ). y = f (x) y = g(x)
[a, b].
Z b
Z b
b

f (x)g (x) dx = f (x)g(x)|a


f (x)g(x) dx.
(52)
a

4.
, , . .
. M R2 . ,
, P , M P .
M (, , ). Int(M ), , M ,
Out(M ), , M . S(P ) P .
S(M ) =

sup

S(P ),

S(M ) =

P Int(M )

inf

P Out(M )

S(P ).

3. M ,
s(M ) = s(M ).
S(M ) = s(M ) = s(M ) .
, :
10. M1 M2 . ,
S(M1 M2 ) = S(M1 ) + S(M2 ),
M1 M2 = .
, :
11. y = f (x) , [a, b] f (x) > 0
x [a, b]. , ,
, x = a x = b,

Z b
f (x) dx.
a

10 11 ,
.

17

16 ( , ). ,
x2 y 2
+ 2 = 1.
a2
b
,
Z a p
b
S=2
a2 x2 dx.
a
a
3,
a

x b p 2
2
S = (ab arcsin + x a x ) = ab.
a a
a

, a = b = R R, R2 .
5. , ,

x = x(t), y = y(t),
t0 6 t 6 t1 ,

Z t1
S=
y(t)x(t)
dt.

(53)

t0

, 0 1 ,

r = r(),

1
S=
2

r 2 () d.

(54)

17.
x = a cos t,

y = b sin t,


Z 0
Z
S=2
b sin t(a sin t) dt = 2ab

sin2 t dt = ab,

, , , 16.
18. r = a. (54)

2
Z
1 2 2 2
a2 3
4
S=
a d =
= 3 aa .
2 0
6
3
0

. ( ) , ,
. , , .
, .

12. N , 11, .
Z b
V (N ) =
f 2 (x) dx.
(55)
a

18

19 ( ).
x2 y 2
+ 2 =1
a2
b
, . (55)

a
Z a 2
b2 2
x3 
4
b
2
2
V =
(a x ) dx = 2 a x
= ab2 .

2
a
3 a 3
a a
, a = b = R R: 43 R3 .

. ,
x = x(t),
y = y(t)
[a, b]. , t [a, b] . [a, b]
a = t0 6 t1 6 6 tn = b

M0 = (x(t0 ), y(t0 )), M1 = (x(t1 ), y(t1 )), . . . , Mn = (x(tn ), y(tn )),
.
p
si = (x(ti+1 ) x(ti ))2 + (y(ti+1 ) y(ti ))2 ,

i = 0, . . . , n 1,

, Mi Mi+1 = max si .
4. ,
P
s = lim n1
(56)
i=0 si .
0

13. , x = x(t) y = y(t)


t.
Z bp
s=
x 2 + y 2 dt.
(57)
a

6.

y = f (x),
x = a x = b
Z bp
s=
1 + (fx (x))2 dx,

(58)


r = r(),

= a = b
Z bq
s=
r 2 () + (r ())2 d.
a

(59)

19

20.
x = At + ,

A2 + B 2 6= 0.

y = Bt + ,

, t = t0 t = t1 , (57)

Z t1 p
p
s=
A2 + B 2 dt = (t1 t0 ) A2 + B 2 .
t0

y = kx + b,
(58)
s=
.

x1
x0

p
1 + k2 dx = (x1 x0 ) 1 + k2 ,

21.
y=

x2
2p

x [0, a], a > 0,



 a
Z as
p

x2
1 1 p 2
p2
2
2
2
s=
1 + 2 dx =
x p +x +
ln(x + p + x ) =
p
p 2
2
0
0

ap 2
p a+
=
p + a2 + ln
2p
2

p2 + a2
.
p

22. r = p
= a (59)
Z ap
p

p p
s=
p2 + p2 2 d = a 1 + a2 + ln(a + 1 + a2 ) .
2
0
23. ,
x = a cos t,

a2 b2
,
a

y = b sin t,

a > b,

0 6 t 6 2.

x 2 + y 2 = a2 sin2 t + b2 cos2 t = a2 (1 2 cos2 t),

, ,

s=a

2
0

(1 2 cos2 t) dt.

. ,
. a = b = R (.. = 0).
, , s = 2R, .
7. ,
x = x(t),

y = y(t),

z = z(t),


Z bp
s=
x 2 + y 2 + z 2 dt.

(60)

.

.

20

. , n m1 , . . . , mn
n
X

K=

(61)

mi di ,

i=1

di i- .

x = x(t),

y = y(t),

t [a, b].

, , , ..
.
Z b
Z b
p
p
2
2
Kx =
y(t) x (t) + y (t) dt,
Ky =
x(t) x 2 (t) + y 2 (t) dt
(62)
a

.
, y = f (x) [a, b] .

Z
1 b 2
Kx =
f (x) dx,
(63)
2 a

Z b
Ky =
xf (x) dx.
(64)
a

. , ,
:
,
. . ,

Rb p
Rb p
2 + y 2 dt
y x 2 + y 2 dt
a x x
= Rbp
,
= Ra b p
(65)
2 + y 2 dt
2 + y 2 dt
x

a
a

Rb
1 a xf (x) dx
= Rb
,
2
a f (x) dx

Rb

f 2 (x) dx
= Rab
a f (x) dx

(66)

.
x = x(t),

y = y(t)

F = F (x, y),
. sF , s ,
Z b
p
W =
F (x(t), y(t)) x 2 + y 2 dt
(67)
a

21

5.
Rb
, a f (x) dx, , (a)
(b) .
. .
.
5. y = f (x) [a, +)
[a, b], a 6 b. ( )
Z b
Z +
f (x) dx = lim
f (x) dx,
(68)
b+ a

, () f (x)
. , .R
a
f (x) dx. ,

Z +
Z a
Z +
f (x) dx =
f (x) dx +
f (x) dx.
(69)

, (69) a R.
.

R + 11. F (x) . a f (x) dx , lim F (b),


b+

(70)

f (x) dx = lim F (b) F (a).


b+


24.
Z +
x dx.

Ra

f (x) dx

R +

f (x) dx.

(71)

11


1 
lim b+1 a+1 ,
+ 1 b+
a
(71) , < 1.
Z

x dx =

.
12. y = f (x) , [a, +). :
R +
R +
1) a f (x) dx, a f (x) dx, a > a, .
Z +
Z a
Z +
f (x) dx =
f (x) dx +
f (x) dx.
a
a
R + a
2) a f (x) dx ,
R +
lim
f (x) dx = 0.
a

R +

3) a
,
Z

a +

f (x) dx

c f (x) dx = c

f (x) dx.

R +
a

cf (x) dx, c

22

R +
R +
R +
f (x)
4)  a f (x) dx a g(x) dx , a
g(x) dx,
Z +
Z +
Z +

f (x) g(x) dx =
f (x) dx
g(x) dx.
a

, [a, +),
:
R +
13. a f (x) dx f ,
Z b
R :
f (x) dx 6 b > a.
a

, +.

.
14.
g(x), 0 < f (x) 6
R +[a, +) f (x)
R +
g(x), a g(x) dx a f (x) dx, R +
R +
a f (x) dx a g(x) dx.
15. f (x) g(x) , [a, +).
lim

f (x)

x+ g(x)

= K,
R +

0 6 K 6 +.

a g(x) dx K < + R +
R +
a f (x) dx, a g(x) dx K > 0
R +
a f (x) dx. , 0 < K < +
.
24 .
3. [a, +) f (x)
f (x) =

g(x)
.
x

:
R +
1) > 1 g(x) , a f (x) dx ;
2) 6 1 g(x) > c > 0, .
4. x + f (x)
R +
a f (x) dx > 1 6 1.

1
,
x

,
.
R +
14. a f (x) dx ,
> 0 b0 > a, b, b > b0

Z

b



f (x) dx < .

b

R +
R +
5. a |f (x)| dx, a f (x) dx.
, 5, .

23

. , . [a, b], , y = f (x)


[a, b ], 0 < < b a.
6.
Z b
Z b
f (x) dx = lim
f (x) dx

(72)

0 a

, () f (x)
. , .
8. , [a, b ],
[a, b], , lim f (x) = . .
xb

, .
. , ,
.
15. F (x) . Rb
a f (x) dx , lim F (x),
xb

(73)

f (x) dx = lim F (x) F (a).


xb

Rb
16. a f (x) dx f
,
Z b
R :
f (x) dx 6 > 0, < b a.
a

, +.

6. [a + , b] f (x)
f (x) =
:

g(x)
,
(x b)

> 0.

1) < 1 g(x) ,
2) > 1 g(x) > c > 0, .

Rb
a

f (x) dx ;

1
7. x b f (x) (xb)
, > 0, Rb
a f (x) dx < 1 > 1.
Rb
17. a f (x) dx ,
> 0 > 0, , , 0 < , < ,

Z

b



f (x) dx < .

b

8.

Rb

a |f (x)| dx,

Rb
a

f (x) dx.

, , 8, .

24

. , ( ), .
. 11, 24.
25.
Z

+
0

dx
= lim arctg b arctg 0 = 2 .
1 + x2 b+

26. (44) ,
Z +
a sin bx b cos bx ax
b
b
eax sin bx dx = lim
e + 2
= 2
,
2
2
2
x+
a +b
a +b
a + b2
0
Z +
b sin bx + a cos bx ax
a
a
eax cos bx dx = lim
e + 2
= 2
.
2
2
2
x+
a +b
a +b
a + b2
0
27.
Z 1
Z a
Z 1
dx
dx
dx

=
+
=
2
2
1x
1x
1 x2
1
a
1
= ( lim arcsin x arcsin a) + (arcsin a lim arcsin x) =
x1

x1

a , (1, 1).
. :
Z b
Z b
f (x) dg(x) = lim (f (x)g(x)) lim (f (x)g(x))
g(x) df (x).
(74)
xa

xb

a, b .
28.
Z
29.
Z
2

1
0

ln x dx = lim x ln x lim x ln x
x1

x0

ln sin x dx = lim x ln sin x lim x ln sin x


x0

x 2

dx = 1.

cos x
x
dx =
sin x

x ctg x dx.

, , , .
. :
[a, b), b +. y = f (x) ,
[a, b ] [a, b).
s = (t) = (a),
= lim(t).
tb

f (x) dx =
a

f ((t)) (t) dt.

, , ,
.
(a, b], (a, b),
(t).

25

30.
Z

x =

a cos2 t

31.

dx
(x a)(x b)

+ b sin t. = 0, = 2 ,
Z b
Z
2
dx
p
=2
dt = .
(x a)(x b)
a
0
Z

dx
1
+
x4
0
. -, x = 1t :
Z 0
Z 0
t2 dt
t2 dt
I =
=
.
4
4
+ 1 + t
+ 1 + t

Z
Z
1 + (1 + x2 ) dx
1 + (1 + x12 ) dx
I=
=
.
2 0
1 + x4
2 0
x2 + x12
I=

z = x x1 :
Z
1 + dz
1
I=
=
lim arctg z2 lim arctg
x+
x
2 z 2 + 2
2 2

z
2

.
2 2

, , . ,
, . .
.
32. 29 ,
Z
2
ln sin x dx
J=
0

. . x = 2t
Z
Z
Z
4
4
4

J =2
(ln 2 + ln sin t + ln cos t) dt = ln 2 + 2
ln sin t dt + 2
ln cos t dt.
2
0
0
0
R
t = 2 u, 2 ln sin t dt.
4
,
Z
Z
4
2

J = ln 2 + 2
ln sin t dt +
ln sin t dt = ln 2 + 2J,

2
2
0
4
..
Z
2

ln sin x dx = ln 2.
2
0
33.

K=

ex dx.

(75)

. , . , (1 + t)et t (0, +)
. t = x2 + 1,
2
1
0 < ex <
.
1 + x2

26

, 25, 0 < K 6 2 .
, , ,

Z +

x2
e
dx =
.
(76)
2
0

6.
( , ) ,
() , .
,
Z b
f (x) dx;
(77)
a

, (77) .

. [a, b] n
,
ba
a = x0 , x1 , . . . , xn = b,
xi+1 xi = h =
,
n
[xi , xi+1 ] . 2, (77),
Z b

b a  f (a) + f (b)
f (x) dx

+ f (x1 ) + + f (xn1 ) .
(78)
n
2
a
(78) .
, ,
, . (78). ,
[a, b],
|| 6

|b a|3
max |f (x)|.
12n2
[a,b]

(79)

(77) .
. n
, ( 2n ). , 2i, 2i+1 2i+2.

Z b

ba 
f (x) dx
(f (a) + f (b)) + +2(f (x2 ) + + f (x2n2 )) + 4(f (x1 ) + + f (x2n1 ) . (80)
6n
a
, .
,

|| 6

|b a|5
max |f (4) (x)|.
180 (2n)4 [a,b]

(81)

Оценить